2011
DOI: 10.1364/ol.36.002104
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear optical properties of carbon nanotube-coated single-mode optical fiber gratings

Abstract: Single-wall carbon nanotube deposition on the cladding of optical fibers has been carried out to fabricate an all-fiber nonlinear device. Two different nanotube deposition techniques were studied. The first consisted of repeatedly immersing the optical fiber into a nanotube supension, increasing the thickness of the coating in each step. The second deposition involved wrapping a thin film of nanotubes around the optical fiber. For both cases, interaction of transmitted light through the fiber core with the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 10 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…In recent years, investigations have been extended also to the optical nonlinearity of CNTs [8]. The literature on this topic is abundant on both the experimental and theoretical sides [9][10][11][12][13], but still remains incomplete on many aspects. The properties of interest are the first and second hyperpolarizabilities, β and γ.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, investigations have been extended also to the optical nonlinearity of CNTs [8]. The literature on this topic is abundant on both the experimental and theoretical sides [9][10][11][12][13], but still remains incomplete on many aspects. The properties of interest are the first and second hyperpolarizabilities, β and γ.…”
Section: Introductionmentioning
confidence: 99%
“…One recent method to increase the mechanical properties of adhesives is through the addition of carbonnanotubes (CNTs). Previous authors have demonstrated CNT coatings on optical fibers, to create nonlinear optical interactions, however not at sufficient densities to significantly change their mechanical properties [10][11][12][13][14][15][16]. Typically, adding CNTs to bulk polymers or coatings results in a maximum performance gain at around a few percent weight addition [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, as excellent materials for surface modification of optical fiber, CNTs have been integrated with various fiber structures, including photonic crystal fiber, tilted FBG (TFBG), and long-period fiber grating (LPG) [18][19][20][21][22]. By exploiting intervention of CNTs with the evanescent field of the above devices, great improvements to refractive index responsivity were demonstrated for chemical and biological parameter measurements.…”
Section: Introductionmentioning
confidence: 99%